Child rearing or childbearing? Risk of cardiovascular diseases associated to parity and number of children - Angelo d'Errico; Dario Fontana; Carlotta Sacerdote; Chiara Ardito (BMC, 2024)
Abstract Background An increased risk of cardiovascular diseases (CVD) has been associated with women's parity, but whether or not this association reflects a direct pregnancy effect, or exposure to factors related to childrearing, still appears unclear. We assessed the CVD risk associated with number of children separately by gender and tested effect modification by socioeconomic position (SEP) and employment status, in order to elucidate the possible mechanisms underlying this association. Methods The study population was composed of 20,904 men and 25,246 women who were interviewed in one of two National Health Surveys conducted in 2000 and 2005 in Italy. These subjects were followed for CVD incidence up to 2014 through record-linkage with national archives of mortality and hospitalisations. CVD risk was estimated by Cox regression models that were adjusted for socio-demographics, perceived health, lifestyles, biological CVD risk factors and for other potential confounders. Results CVD incidence was significantly increased among men with 3 or more children (HR = 1.26, 95% CI: 1.02-1.56) and among women with 2 and with 3 or more children (HR = 1.42, 95% CI: 1.10-1.83; and HR = 1.39, 95% CI: 1.03-1.87, respectively) compared to subjects without children and no significant gender differences were observed. Subjects with lower SEP displayed stronger associations with parity and a higher number of children for both genders; by contrast, no modifying effect of employment status was observed. Conclusions Taken together, the significant association between higher parity and CVD risk in both genders, and the higher risk of CVD associated with higher parity among lower SEP parents, suggests that childrearing has a potential effect on the development of CVD that is more pronounced among disadvantaged families, although a concurrent effect of childbearing cannot be completely excluded.